حساسية ونوعية الموجودات التنظيرية للعفج في تشخيص الداء الزلاقي عند الأطفال - إبراهيم, علي; صهيوني, أمل (Latakia University Journal -Medical Sciences Series, 2014)
تم تعيين عدة مظاهر عيانية أثناء تنظير العفج عند مرضى الداء الزلاقي، أجريت هذه الدراسة من أجل تحديد القيمة التشخيصية لبعض العلامات التنظيرية المشاهدة عند مرضى الزلاقي بهدف استخدامها في التشخيص السريري للمرض كمشعر إضافي يدعم التشخيص. شملت الدراسة 504 أطفال راجعوا بأعراض مختلفة (فشل نمو، إسهال أو إمساك مزمن، فقر دم غير مفسر، نقص وزن)، وخضعوا لإجراء تنظير هضمي علوي. تم تقييم أربع علامات تنظيرية في القطعتين الثانية والثالثة للعفج هي: التحرشف، قلة الانثناءات، المظهر العقيدي، والالتهاب المزمن (البقع البيضاء). شُخص الداء الزلاقي بناء على نتيجة التشريح المرضي للخزعة المأخوذة أثناء التنظير عند 123 مريضاً، تراوحت أعمار المرضى من 6 أشهر إلى 15 سنة. وكانت علامة التحرشف الأعلى حساسية ونوعية 89%، 96% على التوالي. القيم التشخيصية لهذه العلامات بشكل عام (الحساسية91%، النوعية 76%، القيمة التنبئية الإيجابية 56%، والقيمة التنبئية السلبية 97%). لاحظنا أن وجود الداء الزلاقي وكذلك الدرجة النسيجية حسب تصنيف Marsh يتعلق بوجود العلامات التنظيرية. Several appearances were assigned in duodenum during endoscopy in patients with celiac disease, this study was conducted to determine the diagnostic value of some endoscopic markers in celiac patients in order to be used in the clinical diagnosis of the disease an additional factor supporting the diagnosis. The study included 504 children reviewed the different symptoms (failure to thrive, chronic diarrhea or constipation, unexplained anemia, weight loss), and underwent an upper gastrointestinal endoscopy. Four markers were evaluated in the second and third part of the duodenum are: scalloping, reduction of duodenal folds, nodular mucosal pattern, and chronic inflammation (punctate whitish spots) . Celiac disease was diagnosed at 123 patients, which was based on the result of the pathology biopsy taken during endoscopy, the patients ranged in age from 6 months to 15 years. Scalloping was the highest sensitivity and specificity marker of 89% ,96 % respectively. Diagnostic values ​​for these signs in general ( 91% sensitivity, 76% specific, positive predictive value 56 %, and negative predictive value 97% ). We observed that the presence of celiac disease, as well as histological grade rating by Marsh classification respect to the existence of endoscopic markers.